Textual Ornamental Palimpsest and interactive narrative. A Close Reading inside the public sphere. - Μερμίγκη Δήμητρα (Epistēmēs Metron Logos, 2018)
Urban ornamentation serve as the canvas for expressing the readmission of ideological and emotional – aesthetics realms in «Public Sphere». The Greek word «diakosmos» stands for ornament; from an etymological standpoint diakosmos describes the relationship between different realms (cosmos) of existence and the journey across. Artists and public are interconnected with the up-to-date idea of «flaneur» and play this game by their own aesthetic creations in the city field through the «diakosmos» by an interactive narrative.